Overcoming the therapeutic resistance of hepatomas by targeting the tumor microenvironment - Zhang, Jiaxin; Han, Huiqiong; Wang, Lei; Wang, Wenjia; Yang, Mei; Qin, Yanru (Frontiers in Oncology, 2022)
Hepatocellular carcinoma accounts for the majority proportion of primary liver cancer and it is the fourth leading cause of cancer-related mortality in the world, while multifactorial drug resistance is regarded as the major cause which lead to treatment failure of HCC. Accumulating evidence show that tumor microenvironment may explain HCC therapeutic resistance mechanisms by its contents, such as cancer-associated fibroblasts, tumor vasculature, immune cells, physical factors, cytokines and exosomes etc. In recent years, anti-angiogenic drugs together with immune checkpoint inhibitors have shown satisfactory results in HCC patients. However, with the enhancement of the communication between tumor and tumor microenvironment, the heterogeneity of the microenvironment on therapeutic resistance becomes particularly complicated, which suggests a more challenging research direction. Also, it’s reported that the 3D organoids model derived from patients’ biopsies is more intuitively to fully understand the role of TME in acquired resistance. Therefore, in this review, we will not only focus on the mechanisms and targets of therapeutic resistance related to tumor microenvironment contents in HCC, but also make a comprehensive description of 3D models on how it contributes to HCC therapy exploration.